Growth of a Gas Bubble in a Steady Diffusion Field in a Tissue Undergoing Decompression. Issue 6 (1st November 2016) - Mohammadein, Selim A.; Mohamed, Khaled G.
Abstract: This paper presents parameterized study on the growth of a convective gas bubble in tissues of a steady diffusion field. Resulting formulae are obtained analytically, which are valid for constant ambient pressure. It's found that the growing bubble radius is proportional to initial bubble radius, initial concentration difference, diver's average temperature and initial void fraction which is the dominant parameter, while it's inversely proportional to surface tension, viscosity, density ratio and ambient pressure. Comparison to some previous work is performed.